PENGARUH PENGGUNAAN MEDIA FLIPBOOK DIGITAL TERHADAP MINAT BACA PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPAS DI SD INSAN PRESTASI SCHOOL DENPASAR - Atnyana, I Ketut Budi; Budiadnyana, Anak Agung Ngurah; Jayadiningrat, Made Gautama; Suciartini , Ni Nyoman Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using digital flipbook learning media on the reading interest of fourth-grade students in the IPAS subject at SD Insan Prestasi School Denpasar. This study employed a quantitative approach using a quasi-experimental design with the Nonequivalent Control Group Design. The sample consisted of 50 students, including 25 students in the experimental class and 25 students in the control class. Data were collected through a reading interest questionnaire and documentation, and analyzed using descriptive statistics, normality test, homogeneity test, and the Independent Samples t-test with the assistance of IBM SPSS Statistics 27. The results showed that the data were homogeneous, with a significance value of 0.867 (> 0.05). Furthermore, the hypothesis test yielded a Sig. (2-tailed) value of 0.000 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Therefore, it can be concluded that the use of digital flipbook learning media has a significant effect on the reading interest of fourth-grade students in the IPAS subject at SD Insan Prestasi School Denpasar.